The Correlation Between the use of YouTube as Learning Media and Students’ Motivation in Learning English - Hatima, Nurul; Tahir, Muhammad; Sofyan, Ryan Rayhana (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This research explores the relationship between the use of YouTube as a learning medium and student motivation in learning English at SMAN 7 Bulukumba. This research uses a quantitative approach with a correlational design. The sample consisted of 50 eleventh-grade students. The instrument used was a closed-ended questionnaire containing 20 statements, measuring two main variables: YouTube utilization and learning motivation, using a 4-point Likert scale. Descriptive analysis results showed that both variables were in the high category, with an average score of 36.48 for YouTube utilization and 36.16 for learning motivation. The Pearson product-moment correlation test revealed a strong and significant positive relationship between the two variables (r = 0.645; p = 0.001). This indicates that the effective use of YouTube can enhance students' learning motivation, both from intrinsic and extrinsic aspects, such as interest, self-confidence, independence, and active participation in learning.